« Qui sont ces Indiens sauvages ? » À propos de la politique étrangère de quelques peuples d’Amazonie en isolement volontaire - Peter Gow (1958-2021) (Tracés, 2022)
This paper is a reflection on the phenomenon of voluntary isolation in Amazonia, about anthropology’s implication in its formation as a concept, and what anthropologists might profitably say about it as a concrete phenomenon in the world. While knowledge based on ethnographic fieldwork might by minimal or even totally absent for people in voluntary isolation, anthropological research has produced a very impressive understanding of indigenous Amazonian social forms in general, knowledge that can be brought to bear on the question.